Public policy response during COVID- 19 pandemic for SME’s survival in Malaysia / Zulnaidi Yaacob and Rafisah Mat Radzi - Yaacob, Zulnaidi; Mat Radzi, Rafisah (2022)
The paper aims to analyze the extent public policy measures formulated are in line with or match the business challenges experienced by Malaysian SMEs (Small Medium Enterprises) during the COVID-19 pandemic. Through the documentary reviews, this paper analyzes the common problems that SMEs face, the impact of the ongoing COVID-19 pandemic on SMEs’ business performance and the policy responses to address this situation. The findings revealed that policy responses in Malaysia, in certain respects have addressed most challenges faced by SMEs, so there is some encouragement in ensuring that businesses remain viable. As such, this paper further discusses the way forward for SMEs to survive in the post-COVID-19 pandemic, which requires government policies support.